1991
DOI: 10.1136/bjsm.25.4.218
|View full text |Cite
|
Sign up to set email alerts
|

Acute lower leg compartment syndrome.

Abstract: Acute compartment syndromes in the lower leg are well recognized following major trauma. However, although rare, they may occur following seemingly minor sporting injury. A case of acute compartment syndrome, following a football game and affecting the peroneal or lateral compartment, is described, in which prompt diagnosis and treatment led to a satisfactory outcome. The diagnosis and surgical management of acute compartment syndromes are discussed. Early recognition and treatment are important in the prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 16 publications
(1 reference statement)
0
8
0
Order By: Relevance
“…Taken together, our data suggest that the magnitude of serum IL-6 increase during or after exercise should not be considered predictive of complications due to strenuous effort, such as the acute compartment syndrome, with the consequent ischemia and damage to the structures within the compartment (Bertoldo et al 2003;Bidwell et al 1996;Brodsky and Bongiovanni 2000;Fehlandt and Micheli 1995;Kahan et al 1994;Kuklo et al 2000;Leach et al 1967;Lonka and Pedersen 1987;McHale and Prahinski 1994;McKee and Jupiter 1995;Nau et al 2000;Power and Greengross 1991;Presnal and Heavilon 1995;Robinson SJ (2000); Wise and Fortin 1997). In a recent study, Bertoldo et al (2003) reported a case of acute bilateral exercise-induced compartment syndrome of the thigh in a man who had performed a spinning activity for 1 h; the pressure of the anterior compartment was bilaterally elevated, as were the serum levels of muscle enzymes.…”
Section: Discussionmentioning
confidence: 82%
“…Taken together, our data suggest that the magnitude of serum IL-6 increase during or after exercise should not be considered predictive of complications due to strenuous effort, such as the acute compartment syndrome, with the consequent ischemia and damage to the structures within the compartment (Bertoldo et al 2003;Bidwell et al 1996;Brodsky and Bongiovanni 2000;Fehlandt and Micheli 1995;Kahan et al 1994;Kuklo et al 2000;Leach et al 1967;Lonka and Pedersen 1987;McHale and Prahinski 1994;McKee and Jupiter 1995;Nau et al 2000;Power and Greengross 1991;Presnal and Heavilon 1995;Robinson SJ (2000); Wise and Fortin 1997). In a recent study, Bertoldo et al (2003) reported a case of acute bilateral exercise-induced compartment syndrome of the thigh in a man who had performed a spinning activity for 1 h; the pressure of the anterior compartment was bilaterally elevated, as were the serum levels of muscle enzymes.…”
Section: Discussionmentioning
confidence: 82%
“…7,8 Apart from Creighton, Kinder and Bach, 9 the remaining cases of compartment syndrome following an ankle sprain were a result of a rupture of the peroneus longus muscle. [10][11][12][13][14][15][16] Creighton et al 9 described a 17-year-old who sustained an inversion injury of the ankle. The following day there were signs of an acute anterior and lateral compartment syndrome, and he underwent fasciotomy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been described in association with trauma, crush injury, 1 ischemia, and reperfusion episodes. 2 Nontraumatic ACS occurs most commonly in the lower leg, but has also been reported in the forearm following muscle overuse, 3 undue exertion, 4 and bleeding diathesis. 5 It requires urgent diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%